Pengembangan Kreativitas Anak Usia Dini Dengan Menggunakan Permainan Lego Warna Pada Paud Kawanua di Kecamatan Tehoru Kabupaten Maluku Tengah - J.L. Kundre; Enjelika Ifasaksily (Jurnal Ilmiah Wahana Pendidikan, 2022)
The purpose of this study was to find out the increase in early childhood creativity through the development of Color Lego Games at Kawanua PAUD, Tehoru District, Central Maluku Regency. The type of research used in this research is Classroom Action Research (CAR). Based on the results of the class action, it can be concluded that the application of color lego games in the development of early childhood creativity in Kawanua Early Childhood Education, Tehoru District, Central Maluku Regency. cycle I in the activity of installing color lego games shows that Cycle I in the activity of installing color legos shows that the ability of children to appreciate the sense of beauty 4 children get 1 (one) star, 6 children get 2 (two) stars, 3 children get 3 stars ( three), and 2 children get 4 stars (four). 7 Doing it yourself without help 7 children get one star, 5 children get 2 stars (two), 2 children get 3 stars (three), 1 child gets 4 stars (four). Having high imagination, 6 children get 1 (one) star, 6 children get 2 (two) stars, 3 children get 3 stars, and no child gets 4 stars